Inferior humeral head subluxation after acute humeral shaft fractures - Gass, Henry M.; Seilern, Jesse; Cantu, Nicolas; Jones, Corey A.; Moore, Thomas J. (International Journal of Research in Orthopaedics, 2024)
Background: Inferior humeral head subluxation (IHHS) is an abnormal inferior translation of the humeral head with respect to the glenoid. While well described for proximal humerus fractures there is little literature regarding IHHS in humeral shaft fractures and the impact of IHHS on fracture healing during non-operative treatment. This study characterized the prevalence and impact of IHHS among patients with acute humeral shaft fractures at a large urban trauma center. Methods: This retrospective analysis included 62 patients treated conservatively for acute humeral shaft fractures at a single level I trauma center from 2018-2021. Occurrence of IHHS in millimeters was measured radiographically as the distance between the inferior glenoid edge and humeral anatomic neck, a distance greater than 10 mm was considered positive. Demographic data, injury mechanism, AO/OTA fracture classification, risk factors (history of stroke, smoking, diabetes mellitus, radial nerve palsy on presentation, any neurovascular disorder), and failure of conservative management (surgical fixation after a 90-day trial) was recorded. Statistical analyses were performed to evaluate association between risk factors, treatment outcome, and IHHS resolution. Results: At an average follow-up of 18 weeks, IHHS was noted at any time point in 32.3% patients. All cases of IHHS resolved without formal treatment. No factors were significantly associated with the occurrence of IHHS. 17.7% patients failed conservative treatment, only three had IHHS. Conclusions: Although IHHS occurred in one third of the study population, it was not significantly correlated with failed conservative management or the need for surgical intervention. This study expands the scope of this phenomenon to include humeral shaft fractures.